Position of Minorities in Yugoslavia(s) - Obradović, Žarko V. (Sociološki pregled, 2019)
An important part of Yugoslavia’s identity and democratic capacity, along with other features, was the position of persons belonging to minority communities. This Paper will try to establish what was the Yugoslav’s minority policy like in various periods of its existence. The Kingdom of Yugoslavia had to accept the international commitments relating to the protection of minorities, but in practice it treated minorities selectively. In the socialist Yugoslavia, equalising the position of the persons belonging to national minorities, i.e. equal position of nations (‘narodi’) and nationalities (‘narodnosti’) was a part of the general state policy. Issues faced by the FR Yugoslavia (economic crisis, refugees, separatism of the Albanians in KiM, ethnic tensions, bombing of the country, etc.) reduced the level of protection of minorities and undermined the country’s entire minority policy.